An electrophysiological correlate of protein kinase C isozyme distribution in cultured cerebellar neurons - Linden, DJ (J Neurosci, 1992)
Protein kinase C (PKC) is a family of at least seven closely related molecules (isozymes) that vary in terms of their requirements for activation and their distribution among cells of the brain. A striking example of this differential distribution is seen in the cerebellum, where Purkinje cells express PKC-I, an isozyme that is strongly activated by both phorbol ester (PE), and low doses of cis-unsaturated fatty acid (c-UFA), while granule cells predominantly express PKC-II, an isozyme that is strongly activated by PE but not c-UFA. Both Purkinje and granule cells have large, easily recorded voltage-gated K currents. These currents are attenuated by PKC activators in several other varieties of neuron. We hypothesized that the effects of these two PKC activators would be predicted by the distribution of the relevant PKC isozyme, and that the delayed outward rectifier current, IK, would be attenuated by both PE and c-UFA in Purkinje cells, but only by PE in granule cells. This hypothesis was confirmed in perforated-patch recordings. The attenuation produced by both activators could be blocked by application of a specific PKC inhibitor, RO-31–8220, and could not be mimicked by inert forms of PE or c-UFA. To our knowledge, this study represents the first report of an electrophysiological correlate of PKC isozyme distribution.